2018
DOI: 10.1002/pbc.27361
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic benign neutropenia: A phenomenon finds an explanation

Abstract: Ethnic benign neutropenia (ENP) is the most common form of neutropenia (NP) worldwide, if an absolute blood neutrophil count (ANC) of < 1.5 G/L is used as definition. In 2009, ENP was associated with a gene variation in the ACKR1/DARC gene, the same variation that also confers the Duffy-null trait. In 2017, a novel mechanism for ENP was introduced, questioning if ENP is a true neutropenic state, when the body's total neutrophil count (TBNC) is concerned. Here, we summarize the current knowledge of ENP, asking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…These findings support the hypothesis that the relative neutropenia in benign ethnic neutropenia individuals results from ACKR1 ‐null progenitors preferentially differentiating to myeloid cells, leading to activated neutrophils migrating from the blood circulation to the tissues, particularly the spleen (Duchene et al , ; Charles et al , ; Palmblad & Hoglund, ). In order to determine whether this hypothesis explains benign ethnic neutropenia partly or completely, or to determine whether benign ethnic neutropenia is a true neutropenic state, the total number of neutrophils in the body (TBNC) needs to be evaluated, which is still lacking (Palmblad & Hoglund, ).…”
Section: Possible Mechanisms Underlying Benign Neutropeniasupporting
confidence: 76%
See 3 more Smart Citations
“…These findings support the hypothesis that the relative neutropenia in benign ethnic neutropenia individuals results from ACKR1 ‐null progenitors preferentially differentiating to myeloid cells, leading to activated neutrophils migrating from the blood circulation to the tissues, particularly the spleen (Duchene et al , ; Charles et al , ; Palmblad & Hoglund, ). In order to determine whether this hypothesis explains benign ethnic neutropenia partly or completely, or to determine whether benign ethnic neutropenia is a true neutropenic state, the total number of neutrophils in the body (TBNC) needs to be evaluated, which is still lacking (Palmblad & Hoglund, ).…”
Section: Possible Mechanisms Underlying Benign Neutropeniasupporting
confidence: 76%
“…It should be noted that there have been reports of neutropenic individuals without the typical ACKR1 SNP (Reiner et al , ), indicating that some familial neutropenias might be due to other mutations that cause low ANC (Palmblad & Hoglund, ). In addition, the Fy(a−b−) phenotype was found to be overwhelmingly prevalent in neutropenic African Americans, but was also found in one‐third of individuals with normal/high ANC, suggesting additional ANC influences from other genetic traits (Charles et al , ; Palmblad & Hoglund, ).…”
Section: Ackr1 Polymorphism and The Null Phenotypementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have confirmed that the Fy(a-b-) phenotype is the most robust method to identify BEN, and we know that the Fy(a-b-) phenotype has stronger diagnostic utility for BEN than self-identified race or ethnicity [Fy(a-b-) phenotype, 97.36% sensitivity, 95.65% specificity; self-identified race, 65.7% sensitivity, 48.8% specificity]. [23][24][25] In addition, other more recently identified polymorphisms, such as the lead SNP rs9131 on the CXCL2 gene seen in some people of African ancestry, are implicated as drivers of lower ANCs. 26 Although it is well known that genetic polymorphisms are much more strongly associated with lower ANCs than ethnicity, the practice of ascribing the condition of BEN to people solely based on a physician's assessment of skin tone and a comparison with current ANC reference ranges has not changed.…”
Section: Introductionmentioning
confidence: 93%